Current and emerging treatment options for uveal melanoma - Pereira, Patricia Rusa (Dove Medical Press, 2013)
Uveal melanoma (UM) is the most common primary malignant intraocular tumor in adults, with a 10-year cumulative metastatic rate of 34%. The most common site of metastasis is the liver (95%). Unfortunately, the current treatment of metastatic UM is limited by the lack of effective systemic therapy. Options for the management of the primary intraocular tumor include radical surgery as well as conservative treatments in order to preserve visual acuity. For metastatic disease, several approaches have been described with no standard method. Nevertheless, median survival after liver metastasis is poor, being around 4–6 months, with a 1-year survival of 10%–15%. In this review, the authors summarize current and promising new treatments for UM.